Branding para a tomada de decisão de compra no mercado gamer - Botelho, Daniela Ruschel (Universidade do Vale do Rio dos Sinos, 2020)
Observing the fast growth of the market of games in Brazil and in the world, there is a need to understand the branding applied in this market segment. Game brands can benefit from understanding the gamer audience's decision-making process, in relation to their brand, to apply more effective marketing strategies. This research aims to understand how branding interferes in the decision-making process of gamers regarding their choice, between purchasing a console, notebook or computer, focusing on the brands Dell Gaming, Alienware, Playstation 4 and Xbox One. For that, a bibliographic review was carried out on authors of game theory, branding and decision making, culminating in the creation of a matrix of values of importance for decision making. After analyzing the data obtained through a questionnaire, which included a total of 56 participants, and then an in-depth interview, which was attended by 6 people who consider themselves gamers.
Keywords: Tomada de decisão; Gamer; Branding; Marca; Compra; Decision-making; Brand; Purchase